Report of the progress and present state of the geological and agricultural survey of North Carolina - Emmons, Ebenezer, 1799-1863 (W.W. Holden, printer to the state, 1855)
1855 Report of the progress and present state of the survey of the Geological & Agricultural Survey of North Carolina, submitted to Governor Warren Winslow and the Senate. The report, authored by State Geologist Ebenezer Emmons, also included the estimated costs of printing, paper, and engraving of the various documents and maps.